Implementation of health silk road as a form of China's health diplomacy initiative in Indonesia - Afghani, Kevin Al; Nuryananda, Praja Firdaus (Universitas Islam Malang, 2022)
The COVID-19 pandemic has shaken the world since the beginning of the first case in Wuhan City, China. It made the international community urge China to take responsibility for the various actions and measures that came from countries affected by the virus. In this regard, China has established a cooperation initiative in health relations through the HSR (Health Silk Road) under the auspices of the OBOR (One Belt One Road) policy. HSR was considered to have a significant effect in fighting the COVID-19 pandemic virus through its health diplomacy approach in several countries, especially countries that have joined the OBOR policy, such as Indonesia. This paper's objective was to determine the role of HSR as a form of China's diplomacy initiative in establishing a health cooperation relationship with Indonesia to fight the COVID-19 pandemic. This writing focused on writing a descriptive non-numeric narrative with secondary data collection techniques. The HSR approach in Indonesia, such as mask diplomacy and vaccine diplomacy, has proven China's success in restoring its image in the international sphere. The delivery of an impressive amount of health assistance and COVID-19 vaccines to Indonesia showed China's seriousness in dealing with the COVID-19 pandemic.